Análise dos fatores de perdas nos sistemas fotovoltaicos da UTFPR Campus Curitiba - Tonolo, Édwin Augusto (2019)
Growing demand for electricity coupled with concerns about global pollution, is causing countries to invest in more sustainable ways to generate electricity. Photovoltaic solar energy appears as one of the most promising renewable sources on the world stage, where world reports show constant increases in installed power, especially in the world’s most developed countries. For a photovoltaic system to deliver the expected results, several site studies are required to minimize losses. The Federal University of Technology – Paraná (UTFPR) campus Curitiba has two photovoltaic systems installed at its headquarters, one in the center, located on the roof of the Green Office (EV), and another one at Neoville. Merit indices appear as an important calculation method for comparing photovoltaic systems of different magnitudes and locations, with EV’s grid-connected photovoltaic system (SFVCR) average performance ratio of 71.93% while Neoville has 77.79%. In order to determine how much each loss factor impacts on power generation, a series of experiments were performed on the photovoltaic systems. Dirt has been a source of studies and has a strong impact on system performance, both when compared to scheduled cleaning and self-cleaning. For EV, the performance rate increased by approximately 6% for cleaning and 10% for self-cleaning compared to data prior to cleaning. The study revealed that for the center headquarters, the inverter has the highest loss rates, with a maximum efficiency of 92%, which can be explained by being an old model and still uses in its construction a transformer. Because EV is located in the city center, shading losses impacted only 4% as the tallest building was built at a safe distance. Electrical installations were correctly sized for wiring power and length, resulting in 0.45% losses. The angle of inclination and orientation often cannot be corrected, as photovoltaic installations usually follow the roof of the building, such as EV, and the calculated losses were just over 1%. In order to determine the losses due to module degradation and mismatch, a device was used which plots the module’s I-V curve, resulting in losses of 3.81%. At the end of all the work, it was determined that the photovoltaic system has a performance of 69.2%. The experiments were not all performed on the same day, but provide an overview of how the losses are distributed in the studied photovoltaic systems.